EFFECTS OF WORK-FAMILY CONFLICT AND COMPENSATION FOR EMPLOYEE PERFORMANCE MEDIATED BY JOB SATISFACTION ON EMPLOYEES IN THE JABODETABEK REGION - Suci, Bunga Mawati Ahlia; Febriyantoro, Mohamad Trio (Bussman Journal : Indonesian Journal of Business and Management, 2023)
This study aims to determine the effect of work-family conflict on job satisfaction, compensation on job satisfaction, and employee performance in employees in the JABODETABEK area. This study uses a quantitative method with the Structural Equation Modeling model and uses the Smartpls software. Data collection techniques using a questionnaire with a sample obtained as many as 1 32 . The results of this study indicate that work family conflict has a negative and significant effect on job satisfaction, compensation has a positive effect on job satisfaction and job satisfaction has a positive and significant effect on employee performance for employees in the JABODETABEK area